The genus Epidapus Haliday (Diptera, Sciaridae) in New Caledonia, with the description of four new species - Vilkamaa, Pekka; Hippa, Heikki; Mohrig, Werner (Zootaxa, 2014)
The following species of the genus Epidapus Haliday, 1851 are recognized from New Caledonia: Epidapus (s. str.) aciculatus sp. n., E. (Pseudoaptanogyna) angulatus sp. n., E. (s. str.) formosus sp. n., E. (Zuhalia) primus Mohrig, 2004 and E. (s. str.) triquetrus sp. n. The new species are described, and a key to the local species is given.